2020
DOI: 10.1007/s13364-020-00543-6
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and interspecific morphological variation in sympatric and allopatric populations of Mustela putorius and M. eversmanii (Carnivora: Mustelidae) and detection of potential hybrids

Abstract: European mustelids include the European polecat, Mustela putorius, and the steppe polecat, M. eversmanii. Both occur sympatrically in the Pannonian Basin, where M. eversmanii hungarica represents the westernmost part of the latter species and they allegedly hybridize. We investigated the morphological relationships in sympatric and allopatric populations of these mustelids with representative sampling, taxonomic and geographic coverage. We evaluated inter- and intraspecific patterns of morphological differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
(29 reference statements)
3
7
0
Order By: Relevance
“…Finally, we uncover novel features for the polecats from the European mainland. Firstly, there is evidence of introgression between European polecats and Steppe polecats (Figure 4), supporting previous phenotypic analysis where the two species occur in sympatry (Cserkész et al, 2021). Also, there is a suggestion of genetic structure in mainland Europe (Figure 5) where polecats from Italy show a distinct genetic population structure when compared to that of other countries.…”
Section: Discussionsupporting
confidence: 83%
“…Finally, we uncover novel features for the polecats from the European mainland. Firstly, there is evidence of introgression between European polecats and Steppe polecats (Figure 4), supporting previous phenotypic analysis where the two species occur in sympatry (Cserkész et al, 2021). Also, there is a suggestion of genetic structure in mainland Europe (Figure 5) where polecats from Italy show a distinct genetic population structure when compared to that of other countries.…”
Section: Discussionsupporting
confidence: 83%
“…However, in addition to the two putative hybrids identified by Bayesian clustering (#26626, #26714), sample ‘P01’ ( M. putorius , Felsőszölnök, W Hungary) was added as a potential third admixed specimen in this analysis. All three individuals were identified as M. putorius based on morphology (Cserkész et al, 2021). All other samples were assigned to one of the clusters with more than 90% probability (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with that, it was collected in a barely forested, mainly agricultural lowland region, where the environmental conditions seem to be much suitable for M. eversmanii . Unfortunately, this specimen was not included in the morphometric analyses made by Cserkész et al (2021). Additionally, none of the analyses based on SSRs showed this specimen as backcrossed, which clearly highlights the limitation of a handful of SSRs for detecting backcrosses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A classic example of the effect of hybridization on morphological traits are the Darwin finches in Galapagos, where most hybrid individuals have intermediate body size and beak shape compared with the parental species [ 186 ]. Several studies in this review reported intermediate phenotypes, e.g., in cetaceans [ 187 ], mustelids [ 188 ], camelids [ 189 ] and primates [ 181 ]. The presence of admixed individuals with intermediate phenotypes may impede species identification in the field.…”
Section: Discussionmentioning
confidence: 99%